Analisis Dampak Usaha Tenun Ikat terhadap Ekonomi Masyarakat Desa Ensaid Panjang Kecamatan Kelam Permai Kabupaten Sintang - Kaja Kaja; Kardius Richi Yosada; Lois Bona (Ekonomis: Journal of Economics and Business, 2022)
The background of the problem in this research is a culture that is part of the tradition of the Desa Dayak Tribe, namely Tenun Ikat which is owned by the community in Ensaid Panjang Village, Kelam Permai District, unfortunately not all the younger generation in Ensaid Panjang Village, Kelam Permai District are good at making Ikat weaving. this. Ikat weaving is one of the identities of the Dayak Desa community that reflects the preservation of culture that should be passed down to the next generation. Tenun Ikat has a very big appeal from local people as well as foreign people. Therefore, Ikat weaving on the other hand has a very high economic value which can have an impact on the community's economy. The research method used is a descriptive method based on ethnography with a qualitative approach. The target subjects in this study were weavers in Ensaid Panjang Village, totaling 15 people. Data collected using data collection techniques using structured observation, interviews and documentation. Through this technique, the data collection tool uses observation guidelines, interview guidelines and documentation. The data obtained will be analyzed using interactive data analysis with the stages of data collection, data reduction, data presentation and drawing conclusions. The results of the research results from the Ikat Weaving business have a very positive impact on the economic income of the people in Ensaid Panjang Village, as well as the preservation of the Ikat Weaving culture, which is the hallmark of the Dayak Village community, as well as bequeathing to the younger generation so that this Ikat weaving is not extinct by the times.